Does Body Contouring After Bariatric Weight Loss Enhance Quality of Life? A Systematic Review of QOL Studies - Toma, Tania (Obes Surg, 2018)
Massive weight loss following bariatric surgery can result in excess tissue, manifesting as large areas of redundant skin that can be managed by body contouring surgery. This study aims to quantify the effects of body contouring surgery on indicators of quality of life in post-bariatric patients. A systematic review and meta-analysis of the literature revealed on indices of quality of life in post-bariatric patients, before and after body contouring surgery. Body contouring surgery resulted in statistically significant improvements in physical functioning, psychological wellbeing and social functioning, as well as a reduction in BMI. Body contouring surgery offers a strategy to improve quality of life in patients suffering from the functional and psychosocial consequences of excess skin after bariatric surgery.